Aerodynamic parameters across age groups - Jotinder Preet Sandhu (Journal of All India Institute of Speech and Hearing, 1970)
The study was conducted to establish norms on terms of aerodynamic parameters using Aerophone II, as aerodynamic parameters have been found to be providing useful information in the assessment and treatment of dysphonics. Thirty normal females and thirty normal males were taken for evaluating the aerodynamic parameters using Aerophone II (voice function analyzer).